Highly sensitive determination of saquinavir in biological samples using liquid chromatography-tandem mass spectrometry - Burhenne, Jürgen; Riedel, Klaus-Dieter; Martin-Facklam, Meret; Mikus, Gerd; Haefeli, Walter E. (Journal of chromatography, 2003)
A selective and sensitive method for the determination of the HIV protease inhibitor saquinavir in human plasma, saliva, and urine using liquid-liquid extraction and LC-MS-MS has been developed, validated, and applied to samples of a healthy individual. After extraction with ethyl acetate, sample extracts were chromatographed isocratically within 5 min on Kromasil RP-18. The drug was detected with tandem mass spectrometry in the selected reaction monitoring mode using an electrospray ion source and 2H5-saquinavir as internal standard. The limit of quantification was 0.05 ng/mL. The accuracy of the method varied between −1 and +10% (SD within-batch) and the precision ranged from +4 to +10% (SD batch-to-batch). The method is linear at least within 0.05 and 87.6 ng/mL. After a regular oral dose (600 mg) saquinavir concentrations were detectable for 48 h in plasma and were well correlated with saliva concentrations (r2=0.9348, mean saliva/plasma ratio 1:15.1). The method is well suited for low saquinavir concentrations in different matrices.
Online 28 October 2002
Gesehen am 25.05.2021